2020
DOI: 10.1038/s41598-020-70327-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel biomarker of MMP-cleaved prolargin is elevated in patients with psoriatic arthritis

Abstract: Psoriatic arthritis (PsA) is a chronic musculoskeletal inflammatory disease found in up to 30% of psoriasis patients. Prolargin—an extracellular matrix (ECM) protein present in cartilage and tendon—has been previously shown elevated in serum of patients with psoriasis. ECM protein fragments can reflect tissue turnover and pathological changes; thus, this study aimed to develop, validate and characterize a novel biomarker PROM targeting a matrix metalloproteinase (MMP)-cleaved prolargin neo-epitope, and to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…PsA is uniquely characterized by synchronous bone erosions and pathological new bone formation (46). Elevated extracellular matrix (ECM) protein fragments in PsA serum reflect the deregulated bone and cartilage turnover and bear the potential to function as diagnostic biomarkers (46)(47)(48). In agreement with these observations, our study also provided evidence of aberrant collagen metabolism in PsA blood during the active phase of the disease.…”
Section: Discussionsupporting
confidence: 81%
“…PsA is uniquely characterized by synchronous bone erosions and pathological new bone formation (46). Elevated extracellular matrix (ECM) protein fragments in PsA serum reflect the deregulated bone and cartilage turnover and bear the potential to function as diagnostic biomarkers (46)(47)(48). In agreement with these observations, our study also provided evidence of aberrant collagen metabolism in PsA blood during the active phase of the disease.…”
Section: Discussionsupporting
confidence: 81%
“…Data from the Human Protein Atlas (HPA) revealed that PRELP is secreted to the extracellular matrix and may anchor basement membranes to the underlying connective tissue ( 42 ), suggesting its potential function in maintaining normal cellular structure. Besides, previous studies have suggested that PERELP has prognostic value in hepatocellular carcinoma and regulates the extracellular matrix and collagen mineralization in the bone system ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, there were several proteins (96, 32 and 51 in K_sEVs, P_sEVs and PK_sEVs, respectively), which were present only in the sEV proteome but not in the cellular proteome (Figure 5B). P_sEV-specific proteins included, but were not limited to ECM proteins (Tenascin, Prolargin, LOX) [61][62][63], angiogenetic factors (neuropilin-1, Slit3) [64,65] and catalytic enzymes (DPYD, CNDP2) [66,67]. K_sEV specific proteins included Kras, several Ras-related proteins (Rras, Rap-1a, Rab8a Rab14, Rab18, Ralb) and Ephrin family members (Ephb3, Ephb4, Epha4), which are known to be upregulated in cancer cell-derived sEVs [27].…”
Section: Proteomic Profiling Identifies Distinct Protein Signatures B...mentioning
confidence: 99%